Implementation of Tourism Marketing Strategy - Suwignyo Widagdo; Pedro M. de F. Barreto Ximenes; Helmi Agus Salim (LPPM Institut Teknologi dan Sains Mandala, 2024)
This study aims to analyze the influence of leadership style, work environment, and work motivation on employee performance at the Ijen District Office, Bondowoso Regency. This quantitative research involved the entire population of 30 employees, consisting of 25 civil servants and 5 contract workers, using a saturated sampling technique. Data were collected through observation, questionnaires, interviews, and literature review, and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The results show that leadership style (t = 3.621; p = 0.001), work environment (t = 2.271; p = 0.032), and work motivation (t = 2.450; p = 0.021) each have a significant partial effect on employee performance. Simultaneously, these three variables also have a significant effect on employee performance (F-value = 42.675 > F-table = 2.975) with a coefficient of determination of 83.12%. Leadership style emerged as the most dominant factor influencing performance. These findings highlight the importance of improving leadership quality, enhancing the work environment, and strengthening motivation through reward systems to boost employee performance in public institutions. Keywords: leadership style, work environment, work motivation, employee performance